Product development strategies of traditional handicrafts of sanjiang dong ethnic group: a study based on consumer preferences - Liang Xianfei; Zairul Anuar Md. Dawam; Sim, Chee Cheang (Penerbit Universiti Malaysia Sabah, 2024)
This study aims to examine consumer preferences for the traditional handicrafts of the Dong ethnic group in Sanjiang and to provide a theoretical basis for future product development. The research provides an extensive analysis of customer demographics, market demand, and suggestions for improving existing items, derived from interviews and thematic analyses of 40 consumers. The results demonstrate that clients value the cultural significance and traditional craftsmanship of Dong handicrafts, while simultaneously seeking the incorporation of modern design elements to meet individual preferences. This paper asserts that the cultural heritage of Dong handicrafts can be integrated with economic benefits through product diversification, craftsmanship enhancement, branding optimization, and the creation of portable products to meet consumer demands and strengthen market competitiveness.